Tuberculosis and Diabetes Mellitus: A Case Series of 100 Patients (SAARC Journal of Tuberculosis, Lung Diseases and HIV/AIDS, 2011)
Introduction: Tuberculosis and Diabetes mellitus are two public health problems which not only often coexist but have serious implications on each other. DM has an impact on symptomatology, radiological presentation, diagnosis and management of TB. TB has a significant impact on DM, causing unmasking of DM and poor control because of stress or because of drug treatment for TB. Present study attempts to assess this coexistence with regard to the age predisposition, sex preponderance, duration and glycemic control of diabetes and the radiological presentations. Materials and Methods: 100 patients presenting to the Department of Tuberculosis and Chest Diseases, Government Medical College, Patiala, who were suffering from both Tuberculosis and Diabetes Mellitus, were studied. Various parameters considered included age, sex, history of diabetes with regard to the duration and the glycemic control and the radiological presentations. Results: It was found that majority were males (61/100). The age group most commonly involved was the 40-60year group (76/100). Majority had their Diabetes diagnosed before the diagnosis of Tuberculosis (57/100), 23 had diagnosis after TB diagnosis, and 20 simultaneously with TB diagnosis. Out of these 57 diagnosed diabetics, 11 patients had controlled diabetes whereas 46 (87.1%) had uncontrolled diabetes. 32 patients had the typical radiological lesions while 68 had atypical presentations with either lower lobe involvement, multi lobe involvement, cavitations or shadows fanning out from the hilum. Conclusion: TB and DM often coexist together and adversely effect each other. Both need to be managed properly in order to achieve favorable treatment outcome. Key Words: TB; DM DOI: 10.3126/saarctb.v7i2.4404SAARC J. TUBER. LUNG DIS. HIV/AIDS 2010 VII(2) 34-38